Development of artificial intelligence-based physics learning modules on static fluid material to facilitate student learning outcomes - Alzahranitia Annida; Yuvita Oktarisa; Yudi Guntara (Practice of The Science of Teaching Journal: Jurnal Praktisi Pendidikan, 2025)
This study aims to develop a physics learning module based on Artificial Intelligence (AI) on static fluid material to facilitate the learning outcomes of grade XI SMA/MA students. The background of this study is the low learning outcomes of students caused by lack of interest in learning, limited learning media, and the abstract nature of static fluid material that is difficult to understand without the help of interactive and adaptive media. This study uses the Research and Development (R&D) method with a 4D development model modified into three stages, namely define, design, and develop. The product developed is an AI-based learning module with chatbot integration as a virtual tutor, equipped with comics, activity sheets, practice questions, and evaluations that enable independent learning. The validation results from material and media experts show that this module is very feasible to use with a material feasibility value of 4.08 and media of 4.15. Limited trials were conducted on 34 grade XI SMAN 1 Kragilan students with an average response result of 4.46, which indicates a very feasible category. It can be concluded that the developed Artificial Intelligence-based physics learning module is stated to be feasible and effective as an alternative teaching material in physics learning in high school, especially in static fluid material. Abstrak. Penelitian ini bertujuan untuk mengembangkan modul pembelajaran fisika berbasis Artificial Intelligence (AI) pada materi fluida statis untuk memfasilitasi hasil belajar peserta didik kelas XI SMA/MA. Latar belakang dari penelitian ini adalah rendahnya hasil belajar peserta didik yang disebabkan oleh kurangnya minat belajar, keterbatasan media pembelajaran, serta sifat abstrak dari materi fluida statis yang sulit dipahami tanpa bantuan media yang interaktif dan adaptif. Penelitian ini menggunakan metode Research and Development (R&D) dengan model pengembangan 4D yang dimodifikasi menjadi tiga tahap, yaitu define, design, dan develop. Produk yang dikembangkan berupa modul pembelajaran berbasis AI dengan integrasi chatbot sebagai tutor virtual, dilengkapi dengan komik, lembar kegiatan, latihan soal, serta evaluasi yang memungkinkan pembelajaran mandiri. Hasil validasi dari ahli materi dan media menunjukkan bahwa modul ini sangat layak digunakan dengan nilai kelayakan materi sebesar 4,08 dan media sebesar 4,15. Uji coba terbatas dilakukan pada 34 peserta didik kelas XI SMAN 1 Kragilan dengan hasil rata-rata respons sebesar 4,46, yang menunjukkan kategori sangat layak. Dapat disimpulkan bahwa modul pembelajaran fisika berbasis Artificial Intelligence yang dikembangkan dinyatakan layak dan efektif sebagai alternatif bahan ajar dalam pembelajaran fisika di SMA, khususnya pada materi fluida statis.